Prediction of excess enthalpy in binary mixtures through probabilistic matrix completion - Hermanus, Garren Ryan (Stellenbosch : Stellenbosch University, 2025)
Hermanus, G. R. 2025. Prediction of excess enthalpy in binary mixtures through probabilistic matrix completion. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/62ffa814-3bef-4ef0-a940-56a51ed624eb